César Vallejo’s “Trilce” and the Modern Woman - Hibbett, Alexandra (2023)
This article interprets Trilce (1922) by César Vallejo as a reaction to the emergence of the modern woman. By linking the analysis of the poems to a historical reconstruction of the changes that were underway in the social positioning of Peruvian women at the beginning of the 20th century, it explores the female figures of the mother, the sexual woman, the woman who has aborted and the voiceless woman, and shows how Trilce relates them to different aspects of time and modernity. Furthermore, it shows how, when facing these figures, the speaker makes himself visible, with bad conscience, as a subject who is not universal, but male. It is also in the face of these female figures that the poems signal that the encounter with the modern woman is what forces their own poetic style towards its most avant-garde innovations.